Numerical analysis of convergent-divergent nozzle using finite element method - G M, Fharukh Ahmed; Al-Robaian, Abdul Rehman A; Aabid, Abdul; Khan, Sher Afghan (Transstellar Journal Publications and Research Consultancy Private Limited, 2018)
In this paper, Finite element method (FEM) were used to simulate the different flow configuration. Convergent divergent (CD) nozzle was considered with extended divergent duct. 1 mm of micro jets orifice diameter were arranged at ninety degrees at PCD 13 mm to control base pressure in a suddenly expanded flow. The designed Mach number of CD nozzle is 1.87 and area ratio 3.24 was considered. The different L/D of the duct was used from 2 to 10. The nozzle pressure simulated for 3, 5, 7, 9 and 11. In this case. Two-dimensional planar model was designed using ANSYS fluent analysis. The total wall pressure distribution and Mach number from inlet to the outlet was observed. From the results, it is detected that the micro jets control the loss of pressure and decreases the drag at the suddenly expanded region. The results also show, we can fix the flow parameter which will result in the maximum gain in the base pressure and velocity. In present study, the CD nozzle designed and modelled using available ANSYS fluent database: K-ε standard wall function turbulence model has been used and validated with the commercial computational fluid dynamics (CFD)